Anaemia in Ruminants Caused by Plant Consumption - Héctor Ruiz; Delia Lacasta; Juan José Ramos; Hélder Quintas; Marta Ruiz de Arcaute; María Ángeles Ramo; Sergio Villanueva-Saz; Luis Miguel Ferrer (Animals, 2022)
Plant toxicology has affected animals throughout evolution. Plants have adapted themselves to the environment. This adaptation has led to the development of defensive strategies to avoid being consumed. Plants have several chemical compounds, which can cause deleterious effects on people or animals that consume them, causing a wide variety of clinical signs. Plants from various latitudes, both cultivated for human and animal feeding or decorative purpose and even wild growth plants are able to generate anaemia in ruminants. Coumarins or ptaquiloside predispose bleeding and haemorrhages, causing a haemorrhagic disease in affected animals. In this group, some important fodder plants, such sweet clover (Genus Melilotus spp.), or other weeds distributed worldwide, such as bracken fern (Pteridium aquilinum) of giant fennel (Ferula communis), are included. On the other hand, sulfur-containing chemicals (e.g., n-propyl disulfate and S-propyl cysteine sulfoxides (SMCOs)) may cause severe direct damage to the erythrocyte and their membrane, leading to their destruction and causing haemolytic anaemia in the animal. This review presents the most frequent intoxication by plants causing anaemia in ruminants. Toxic compounds, clinical signs, diagnosis and possible treatments are also presented.